2021
DOI: 10.1002/app.50610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mica modification with ethylene‐vinyl acetate wax on the water vapor barrier and mechanical properties of poly‐(butylene adipate‐co‐terephthalate) nanocomposite films

Abstract: Poly-(butylene adipate-co-terephthalate) (PBAT) is one of the most popular raw materials for degradable plastic films because of its good biodegradability, ductility, and processability. However, the application of this material is limited by its unsatisfactory water vapor barrier property. This study aims to improve the water vapor barrier and mechanical properties of PBAT films by introducing mica modified by ethylene-vinyl acetate copolymer waxes (EVAmica). The EVA-mica nanosheets showed a more uniform disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…As a complex, non-isothermal, and non-uniform biaxial extensional process, film blowing involves the orientation of polymer chains and fillers in the melt state, which can then be kinetically trapped upon cooling. [179,180] Through orienting filler particles in the composite films, the properties of resulting films can be improved. [178] For example, this method can be used to prepare nylon 6/clay nanocomposite films with clay layers aligned in parallel to their long axis to the film surface (Figure 2).…”
Section: Film Blowingmentioning
confidence: 99%
“…As a complex, non-isothermal, and non-uniform biaxial extensional process, film blowing involves the orientation of polymer chains and fillers in the melt state, which can then be kinetically trapped upon cooling. [179,180] Through orienting filler particles in the composite films, the properties of resulting films can be improved. [178] For example, this method can be used to prepare nylon 6/clay nanocomposite films with clay layers aligned in parallel to their long axis to the film surface (Figure 2).…”
Section: Film Blowingmentioning
confidence: 99%
“…Even if micas do not expand in water due to the strong electrostatic interaction between the layer’s negative charge and the interlayer K + ions [ 19 ], to improve the dispersion and compatibilization with the polymeric matrix, organic (i.e., with ethyl-vinyl-acetate [ 20 ] or diacetone-acrylamide [ 21 ]), organometallic (i.e., with triethylaluminum [ 22 ]) or inorganic (i.e., exchanging with metal cations [ 23 , 24 ]) modifications together with the addition of different coupling agents (i.e., maleic anhydride [ 25 ] or silane [ 26 ]) have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The organic layer can develop on the surface of mica through the use of coupling agent, which is effective in improving the dispersion of mica and the compatibility with polymer matrix. By treating mica with EVA wax, Wang et al 16 enhanced the gas barrier properties of PBAT blended films by 80.1% and the mechanical strength by 26.8%. Xia et al 17 prepared PBAT/PPC/mica blend films and found that the mechanical and gas barrier properties of films containing mica were greatly improved after stretching treatment.…”
Section: Introductionmentioning
confidence: 99%